Pengaruh Lingkungan Kerja Non Fisik dan Disiplin Kerja terhadap Kinerja Pegawai Kantor Kelurahan Malanu, Kota Sorong - Renouw, Ade Andriani; Sinay, Philipuis; Mansoben, Helonia Diana (Innovative: Journal Of Social Science Research, 2025)
The purpose of this study is to analyze the influence of non-physical work environment and work discipline, on the performance of Sorong City employees, the data analysis method used is quantitative descriptive analysis. The results of the t-test, the independent variable partially, the t-count value of the non-physical work environment has a positive/significant effect on the dependent variable, where the t-count value of the non-physical work environment variable is tcount 4.561> from ttable 1.6716, or the significance value is 0.000 smaller than 0.05. This means that because t-count> t-table, it can be concluded that the hypothesis (H1) is accepted, the work discipline variable is tcount 2.931> from ttable 1.6716, or the significance value is 0.000 smaller than 0.05. This means that because t-count> t-table, it can be concluded that the hypothesis (H2) is accepted. The results of the F test obtained an Fcount value of 24.642 with a significance of 0.000. shows significance <0.05. means that non-physical work environment and work discipline simultaneously affect the performance of employees at the Malanu Village Office, Sorong City.